Tratamento de esgoto de uma unidade universitária com tanques sépticos seguidos de leitos cultivados com diferentes meios de suporte - (:unkn) unknown (Universidade Estadual de Goiás, 2011)
The present study had the goal of assessing three compartmentalized septic tanks (TSC) installed in series, followed by three wetlands (LC) with species Typha sp. (Taboa), with subsurface flow, constructed in parallel and filled with support material natural gravel, gravel # 2 and washed gravel, with the porosity of 54%, 48% e 38%, respectively, and hydraulic retention time of 24 hours. The study was conducted at Unity University for Science and Technology, State University of Goiás – UnUCET/UEG. The septic tanks are constructed of a polyethylene box and two fiber boxes with a useful volume of 12,4 m3; 8,3 m3 e 4,6 m3, respectively. The wetlands have the dimensions 6 m x 2 m x 1 m (length, width and depth) with useful volume of 5,8 m3; 5,2 m3 e 4,56 m3, respectively. The evaluation system was performed in the period of October and November of 2010 and April and May of 2011, analyzing the biological, chemical and physical variables of the sewage, in the outputs of the three septic tanks and three wetlands totaling seven points of analysis. We also evaluated the dry mass and root growth at the end of the experiment. The results were analyzed by the Statistical Analysis System (SAS program), by applying the Tukey test at 5% probability. There were no meaningful differences in the removal efficiency in the parameters analyzed in LC’s. The TSC showed an increase in the amount of alkalinity, low removal capacity for the parameters nitrite (NO2-), nitrate (NO3-), sodium (Na+), chemical oxygen demand (COD) and higher removal capacity for total solids (TS), fixed solids (STF), total suspended solids (TSS), turbidity, biochemical oxygen demand (BOD), total coliforms (TC) and fecal coliforms (CTemo). The LC’s showed a higher removal capacity for TSS, turbidity, BOD, TC e CTermo, followed by smaller decreases for ST, STF, NO2-, NO3-, PO43-, COD and Na+ and increased alkalinity. For the parameters pH, turbidity, NO2-, NO3-, PO43-, BOD and heavy metals was reached the limits established by CONAMA Resolution n. 430/2011. The evaluation of plant growth showed the adaptation of the materials of support macrophytes and sewage, with higher dry matter production in the bed filled with natural gravel. The use of three different materials of support in LC’s did not significantly affect the removal of the parameters, indicating the possibility of using natural gravel and washed gravel as alternatives to the materials of support in LC’s.
Keywords: Zona de raízes; Macrófitas; DBO; Remoção de sólidos; Roots zone, .; Macrophytes; BOD; Solids removal; ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO; ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL